Knowledge of orofacial pain in students of the Dental Professional Program Faculty of Dental Medicine, Universitas Airlangga - Desvia Nuzela Qurzani Hariyadi; Ari Hapsari Tri Wardani; Saka Winias; Fatma Yasmin Mahdani; Adiastuti Endah Parmadiati; Nurina Febriyanti Ayuningtyas; Meircurius Dwi Condro Surboyo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: Orofacial pain is associated with the hard and soft tissues of the head, face, and neck. Knowledge of orofacial pain helps in getting information on clinical symptoms, trigger factors, and risks of orofacial pain, as well as clinical and supportive examinations for identifying the pain. The dental professional students’ knowledge influences the ability to diagnose and decide on an appropriate treatment plan. This knowledge is seen from the intelligence level in obtaining information about orofacial pain. Purpose: To describe the level of knowledge of orofacial pain in the students of the Dental Professional Program, Faculty of Dental Medicine, Universitas Airlangga, based on intelligence level. Methods: This research was a descriptive study. Data was taken using a questionnaire on google form with a simple random sampling data technique and was analyzed using SPSS version 25. Results: The majority understand the general description of postherpetic neuralgia (PHN), as well as the risk factors and triggers (93.4% and 87.8%, respectively) associated with it. Further, 90.6% understand burning mouth syndrome (BMS) and the clinical symptoms of PHN. BMS based on clinical examination and support is understood by 96.1%, and 82.9% know how to manage trigeminal neuralgia (TN). Intelligence level is divided into three categories, namely source of knowledge (55.8% are from lectures, journals, and textbooks), material repetition (77.3% never repeated), and retention of material (65.2% no retention). Conclusion: Students’ knowledge of orofacial pain is good, but the relationship between the level of intelligence and knowledge is not yet known.